Building Brand Equity on Halal Cosmetics Brand in Indonesian - Rina Dewi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study is to determine whether there is a relationship between brand image and brand trust on brand equity through brand loyalty to halal cosmetics brand. Research methodology is quantitative methods with 224 samples consumers who have criteria to be active users for a minimum of 2 years, and make purchases at least twice in a year. Analysis technique uses the Structural Equation Model with 2 exogenous variables with 10 observed variables and 2 endogenous variables with 10 observed variables, data processing with software Stata 14. The results showed that brand image and brand trust have an important part in the formation of brand loyalty. The attitude of loyal consumers towards the halal cosmetics brand acts important to strengthen of brand equity which is a long-term strength advantage for the company. Halal cosmetics are a necessity for Indonesian women to help their appearance beauty and consumers build trust that halal products have the image of being safe and healthy product to use. These findings are beneficial for management science, especially in marketing management so that the company continues have to build a positive brand image, strong brand trust to provide value to consumers, and building strong commitment between the consumer and the halal cosmetic brand.